A (in)constitucionalidade da incidência do imposto sobre serviços (ISS) sobre a tecnologia streaming – uma análise sobre a lei complementar nº 157, de 29 de dezembro de 2016 - Lima, Francisco Eugênio Costa de (Universidade Federal Rural do Semi-Árido, 2017)
The presente work has as aim to study the legislative atualization that extended the incidence of the Tax on Services (ISS) to the operantions of multimedia content availability through streaming tecnology, in order to verify if it obeys the Constitution of the Federative Republic of Brazil’s precepts. Therefore, we first observed basic concepts about tax law, then undergoing to study about the rule of incidence of the Tax on Services, with emphasis in its material criterion. In a second moment, was discussed on streaming tecnology, highlighting its conceptualization, operation and modalities. Then was proceeded to the characterization of the provision of services in the legal-tax system. Next, was verified the terms in which the new legislation included the technology streaming as service chargeable of the Tax on Services. Finally, to analyze the legal nature of the streaming technology to verify whether it can be characterized as a service provision and if it's constitutional, in this way, an incidence of the ISS on it. As for research techniques, it is based on the use of indirect documentation, with the use of legislation, doctrine and jurisprudence on the subject of the research. It concludes, based on constitutional and tributary precpts, as well as on private law, that it is unconstitutional the ISS incidence on streaming, considering that this tecnology can not be characterized as a service provision.
Artigo Acadêmico
Keywords: Imposto sobre serviços; ISS; Streaming; Inconstitucionalidade; Tax on services; ISS; Streaming; Unconstitutionality; CIENCIAS SOCIAIS APLICADAS::DIREITO